ENGLISH AS A STUDENT LITERATION ELECTABILITY: STUDY OF THE ABILITY OF LITERATION IN INDONESIA'S PISA (PROGRAM FOR INTERNATIONAL STUDENT ASSESSMENT) INDEX - Naufal Atha Haidarbahy (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
This study discusses the important role and what are influences the overall reading ability of Indonesian students and their effect on electability competencies that impact PISA reading index, especially in the ability of reading English texts. Indonesian students generally only have a cumulative literacy index of 397 in 2015 which rose only one point from the cumulative literacy index in 2012 which is still relatively low among countries that follow the PISA assessment. This reflects the electability of students literacy who have not reached expectations yet. The literacy skills of Indonesian students in English with the relationship to the PISA index isinfluenced by several factors such as the state of reading, level of reading interest, intelligence or intellectual ability, social background, economic and reader culture, reading abilities and habits and ability to absorb new reading. These factors creates continuity in the important role of building electability literacy, namely to create an objective culture, critical and open mind comprehensively in its application in various realms of activity. Knowing that anything which affects literacy skills also needs to be considered that impedes literacy skills such as no language and code similarity between the writer and reader, communication failure, disruption to speech tools, the system of educational institutions that lack sufficient opportunities for reading traditions and socio-economic factors. And nowadays when the 'borderless world' paradigm globalizes society, there must be language alignment tools in literacy, namely English, so thatthe ability of English language literacy should be obeyed, especially students to understand the importance of English electability in positioning Indonesian students to compete with other countries in literacy skills.